International Panel Forum at The 2014 ACA Conference & Expo, March 27-30 Honolulu. Hawaii Convention Center /the Hilton Hawaiian Village - Rais, Haniza (American Counseling Association, 2014)
Invited international panel at the American Counseling Association Conference 2014 representing Malaysia on Counseling from Malaysian perspective.